Patient and clinician experiences with the implementation of telemedicine and related adaptations in office-based buprenorphine treatment during the COVID-19 pandemic: a qualitative study - Melissa Davoust; Angela R. Bazzi; Samantha Blakemore; Juliana Blodgett; Anna Cheng; Sarah Fielman; Kara M. Magane; Jacqueline Theisen; Richard Saitz; Alicia S. Ventura; Zoe M. Weinstein (Addiction Science & Clinical Practice)
Abstract Background Deaths from opioid overdose have increased dramatically in the past decade. For individuals with opioid use disorder (OUD), agonist medications such as methadone and buprenorphine reduce opioid-related morbidity and mortality. Historically, the provision of buprenorphine treatment in office-based settings has relied on frequent in-person contact, likely influencing patients’ access to and retention in care. In response to the COVID-19 pandemic, providers of office-based buprenorphine treatment rapidly adapted their care processes, increasingly relying on telemedicine visits. To date, relatively few prior studies have combined patient and clinician perspectives to examine the implementation of telemedicine and related care adaptations, particularly in safety-net settings. Methods Qualitative methods were used to explore clinician and patient experiences with telemedicine in an office-based buprenorphine treatment clinic affiliated with an urban safety-net hospital. From this clinic, we conducted semi-structured interviews with 25 patients and 16 clinicians (including prescribers and non-prescribers). We coded all interview data and used a thematic analysis approach to understand how telemedicine impacted treatment quality and engagement in care, as well as preferences for using telemedicine moving forward. Results Five themes regarding the implementation of telemedicine and other COVID-19-related care adaptations arose from patient and clinician perspectives: (1) telemedicine integration precipitated openness to more flexibility in care practices, (2) concerns regarding telemedicine-related adaptations centered around safety and accountability, (3) telemedicine encounters required rapport and trust between patients and clinicians to facilitate open communication, (4) safety-net patient populations experienced unique challenges when using telemedicine, particularly in terms of the technology required and the need for privacy, and (5) there is an important role for telemedicine in office-based buprenorphine treatment moving forward, primarily through its use in hybrid models of care which integrate both in-person and virtual visits. Conclusions Telemedicine implementation within office-based buprenorphine treatment has the potential to improve patients’ engagement in care; however, our findings emphasize the need for tailored approaches to implementing telemedicine in office-based buprenorphine treatment, particularly within safety-net settings. Overall, this study supports the maintenance of changes to policy and practice that facilitate the use of telemedicine in office-based buprenorphine treatment beyond the COVID-19 public health emergency.